Determining concentrations of components of a mixture - Henry, M (United States Patent and Trademark Office, 2014)
Systems and methods for determining concentrations of components of a multiphase fluid. A first flowmeter receives a fluid flow and generates measurements of the fluid flow. After at least partially separating the fluid flow into mixtures of its components, second and third flowmeters generate measurements of the mixtures. A data processing apparatus operatively coupled to the flowmeters receives the measurements and determines concentrations of the components of the fluid flow. In an embodiment, the measurements are mass flow and density readings.